Evaluation of the evidence on staging imaging for detection of asymptomatic distant metastases in newly diagnosed breast cancer - Brennan, M.E.; Houssami, N. (Breast (Edinburgh), 2012)
While guidelines recommend against routine use of staging imaging to detect asymptomatic distant metastases (DM) in newly diagnosed breast cancer (BC), modern imaging technologies may have improved detection capability and may have a role in some cases. We performed a systematic review of studies (1995–2011) evaluating the prevalence of DM and the accuracy of staging imaging for detection of asymptomatic DM. Twenty-two studies reporting on 14,824 BC subjects (median age 53 years) undergoing staging imaging were eligible. Median prevalence of DM was 7.0% (range 1.2–48.8%); prevalence increased with increasing BC stage. Conventional imaging studies had lower DM prevalence than studies of PET(PET/CT). Imaging median sensitivity/specificity respectively were: combined conventional imaging 78.0%/91.4%; bone scintigraphy 98.0%/93.5%; chest X-ray 100%/97.9%; liver ultrasound 100%/96.7%; CT chest/abdomen 100%/93.1%; FDG-PET 100.0%/96.5%; FDG-PET/CT 100%/98.1%. Low prevalence of DM was seen in Stage I–II BC with much higher prevalence in more advanced disease. Accuracy of PET modalities was very high however the high proportion of detected asymptomatic DM partly reflects selection bias.